Formation of palladium nano-gap on self-cracked WO3 for hydrogen gas sensors - Kim, Noeul; Cho, Hyeon Ho; Kim, Youngho; Hwang, Jongkook; Choi, Jae Young; Yu, Hak Ki (International Journal of Hydrogen Energy, 2023)
In the event of a hydrogen leak accident, an explosion occurs at a concentration of 4% or more in the atmosphere, so, the technology to accurately measure the hydrogen detection near the 5% area is very important. Among the various hydrogen detection methods, a hydrogen sensor using a fine pattern of Pd with excellent ability to absorb hydrogen is very suitable for this purpose. In this study, in forming a micropattern of Pd metal, a technique for easily fabricating Pd micropatterns was proposed by utilizing micro-cracks generated in the process of forming a ceramic thin film on a polymer substrate. It showed very accurate detection capability at the 1–5% hydrogen concentration level, and it is expected that it can be easily applied to various curvature environments as it is manufactured on a polymer substrate.
Keywords: Gas-sensors; H2 gas sensor; Hydrogen detection; Hydrogen gas sensors; Hydrogen leak; Micro pattern; Nanogaps; Pd nano-gap; Polymer substrate; Self-cacked template; H2 gas sensors; Pd nano-gap; Self-cacked template